Impacts of outdoor landscape on early learning: insights from the NCDRC kindergarten at UPSI - Hussain, Mohd Amirul; Md Yasir, Ahmad Shah Hizam; Kamaruzaman, Mohd Yusof; Abdul Raji, Mohd Nazri; Basri, Azizul Qayyum; Hanapi, Zaliza; Mohd Yunos, Mohd Yazid (International Information and Engineering Technology Association, 2024)
This study was set on the National Child Development Research Centre (NCDRC) Kindergarten, Universiti Pendidikan Sultan Idris (UPSI), to identify the role of the outdoor landscape in shaping the sense of place and assisting the T&L process of children. Qualitative research design with 15 informants from UPSI's Department of Development and Asset Management (DDAM) and kindergarten teachers were interviewed, revealing themes in outdoor landscapes impact in children's physical, cognitive, emotional, and social development educationally. The study emphasizes the importance of landscape design for holistic child development, compelling kindergarten authorities and the Ministry of Education to prioritize landscape designs in kindergartens.